Variabilitas Genetik Populasi Kedelai Kuning dan Hitam pada Tiga Konsentrasi Pupuk Pelengkap Cair - Affandi, Ari; Rasyad, Aslim (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
The objectives of this study were to determine the components of variances, heritability and selections responce of several traits in a soybean population applied by liquid foliar fertilizer (LFF). A field  experiment was conducted  in the Faculty of Agriculture Experiment Station, University of Riau from February to May 2018 using a split plot design with three replications. Three rates of LFF concentrations applied to plant leaves; ie, no LFF, 2 g.l-1 and 4 g.l-1 were a signed as main plot and eight varieties were assigned as subplot. Seed of every cultivar was panted in a plot of 3 m long and 2 m wide with planting space of 40 cm x 20 cm on February 2018. In the control treatment, inorganic fertilizer was applied according to recommended rate; ie, 25 kg N, 30 kg P2O5, and 30 kg K2O per ha, respectively while for plots applied by LFF, the fertilizer was only applied by one half of recommended rate. Characters observed were plant height, flowering date, number of primary branches, harvest date, number of filled pods per plant, number of seeds per plant, seed weight per plant, seed filling rate, effective seed filling periods, grain yield and hervest index. Data were analyzed by analysis of varians and further tested by least significant different at 5% level. The component of variance and heritability were estimated by the procedure of Hallauer et al. (2004). The result indicated wide variability among varieties for all characters while LFF affected only on  number of primary brunches, plant high, flowering date, grain yield and harvest index. The value of genetic variance was significant for all traits and heritability value was different from zero for all characters. Predicted response to selection was quite high for  number of filled pods per plant and  number of seeds per plant but quite low for other characters. The result indicated that all characters could be used as selection criteria in a plant breeding program. However, number of seeds per plant  and number of filled pods per plant as selection criteria were potential to speed up in reaching plant breeding objective.  Keywords : varians component, heritability, black soybean, selection response